The impact of intangible capital on productivity and wages: Firm level evidence from Peru; El impacto del capital intangible en la productividad y los salarios: evidencia a nivel de empresas de Perú - Rafael Castillo; Gustavo Crespi (Estudios de Economía, 2024)
In the past decades, intangibles assets have become an important source of productivity and economic growth in developed countries. Despite the transforming properties of intangibles across economies and the large and dynamic literature on the impact of intangible investments on productivity growth in frontier countries, there is not much evidence for the Latin America context. This paper contributes to the empirical literature on intangible investments along various dimensions. First, we make use of a large firm-level longitudinal data set from Peru, a Latin America middle income country, which contains separated information on intangible assets, which allow us to measure the impact of them on both wages and productivity at the firm level. Second, the analysis at the firm level and the panel structure of the data allows us to control for the endogeneity of variable inputs applying different control function approaches. In addition, the production function estimates provide us with a measure of unobservables, which we include in the wage equation to retrieve consistent estimates for the impact of intangible assets on wages. Third, our data allow us to explore how the impact of intangibles on wages and productivity is affected by the differences in the composition of the bundle of intangibles, changes in the product mix at the firm level and for the presence of imperfect competition in the labor market. We find that an increase in the share of intan-gible assets by one standard deviation is associated with 6.8% to 7.2% higher total factor productivity, depending on the model's specification. We also find that the capital productivity premium of intangible assets over tangible ones is substantial with estimates suggesting that intangibles are up to 2 times more productive than tangible assets. We also find that this capital productivity premium is not entirely offset by an increase in wages. Finally, we conclude that the main channels for appropriability are the specificity of the ideas generated by intangible investments at the firm level and the wage compression due to imperfect competition in the labor market.
Keywords: D24; E22; O30; O47; 330; Productivity; capital; intangible assets; production function; wages; R&D; firms; spillovers